NGTS 15b, 16b, 17b, and 18b: four hot Jupiters from the Next-Generation Transit Survey. Issue 4 (30th March 2021) - Tilbrook, Rosanna H; Burleigh, Matthew R; Costes, Jean C; Gill, Samuel; Nielsen, Louise D; Vines, José I; Queloz, Didier; Hodgkin, Simon T; Worters, Hannah L; Goad, Michael R; Acton, Jack S; Henderson, Beth A; et al.
ABSTRACT: We report the discovery of four new hot Jupiters with the Next-Generation Transit Survey (NGTS). NGTS-15b, NGTS-16b, NGTS-17b, and NGTS-18b are short-period ( P < 5 d) planets orbiting G-type main-sequence stars, with radii and masses between 1.10 and 1.30 R J and 0.41 and 0.76 M J, respectively. By considering the host star luminosities and the planets' small orbital separations (0.039–0.052 au), we find that all four hot Jupiters are highly irradiated and therefore occupy a region of parameter space in which planetary inflation mechanisms become effective. Comparison with statistical studies and a consideration of the planets' high incident fluxes reveal that NGTS-16b, NGTS-17b, and NGTS-18b are indeed likely inflated, although some disparities arise upon analysis with current Bayesian inflationary models. However, the underlying relationships that govern radius inflation remain poorly understood. We postulate that the inclusion of additional hyperparameters to describe latent factors such as heavy element fraction, as well as the addition of an updated catalogue of hot Jupiters, would refine inflationary models, thus furthering our understanding of the physical processes that give rise to inflated planets.